Owning Ourselves and Encountering Others: Authenticity, Indifference, and Desire - KAREN ROBERTSON (PhaenEx: Journal of Existential and Phenomenological Theory and Culture, 2013)
There are resources in Heidegger’s work for identifying and mitigating pervasive modes of misrecognition that are characteristic of modern society, and, by identifying them, we become capable of attending to “supplementary” aspects of authenticity: terms of identity should apply to all in the same way, and, because these terms are a product of all, they are the responsibility of each individual. The first section analyses Being-guilty, Dasein-with, and Being-with to emphasise Dasein’s dependence on others, arguing that the dynamic of recognition characteristic of Dasein implies a responsibility for recognising the other adequately. The second identifies common modes of misrecognition, arguing that these modes imply a shared responsibility for the contexts of recognition in which we participate. The third turns to Sartre’s work, arguing that our interpersonal relations offer resources for correcting our inadequate ways of recognizing one another and for recognizing the fundamental place of communication in the realization of human freedom.